Pengaruh Budaya Organisasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior Pegawai di Kantor Otoritas Pelabuhan Utama Belawan - Sri Maya Sopha; M. Rajab Lubis; Sjahril Effendy Pasaribu (Mahesa Research Center, 2022)
The purpose of this study was to determine the effect of organizational culture and job satisfaction on organizational citizenship behavior. This research method uses quantitative methods. The population is 115 and the sample is 115 employees with total sampling technique. The results showed that there was a significant influence between organizational culture on organizational citizenship behavior seen from the value of t count t table that is equal to 5.587 with t table of 1.981 and significance 0.000 0.025. Furthermore, there is a significant effect between job satisfaction on organizational citizenship behavior seen from the value of t count > t table that is 3.379 with t table 1.981 and significance 0.001 < 0.025. Lastly, simultaneously there is a significant influence of organizational culture and job satisfaction on organizational citizenship behavior seen from the value of the determinant coefficient (R²) = 0.947 with p = 0.000 < 0.050 with the contribution of organizational culture and job satisfaction to organizational citizenship behavior of 94.7%. These results are reinforced by the results of the F test where the calculated F value > F Table is equal to 1001,869 with an F table of 3,077 and a significance of 0.000 < 0.050